Islamic Education Values in Ziarah Kubur Tradition of Javanese People - Matrokhim Matrokhim (Lakpesdam PCNU Kota Salatiga, 2020)
This study discusses the values of Islamic education in the ziarah kubur tradition of Javanese people in Ngemplak Kumpulrejo, District Argomulyo, and Salatiga city. The focus studied in this research is how the history of ziarah kubur in Islamic teachings, what are the rituals found in the ziarah kubur in Ngemplak Kumpulrejo, Islamic education values of any kind found in the ziarah kubur in Ngemplak Kumpulrejo. This qualitative research uses field research methods, where the researchers becomes very important as researchers act directly as direct instruments and as a data collector of observation results and actively involved in the research. From the research conducted the following research results: Islamic educational values contained in the ziarah kubur tradition in Kumpulrejo, is that there is a mixture of Islamic traditions and Javanese culture that is integrated into a tradition that goes hand-over beautifully without eliminating the significance of the value of Islamic traditions and Javanese culture. And from the procession of the ziarah kubur tradition of Javanese people, especially in Ngemplak Kumpulrejo, contain the values of Islamic education such as faith, Birrul Walidain, the value of education so that people always submit to the world and the value of social education. And then is expected to be taken from the procession of ziarah kubur traditions.